2011
DOI: 10.1007/s12070-011-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery in Chronic Rhinosinusitis and Nasal Polyposis: A Comparative Study

Abstract: Nasal polyposis are common presentations in patients of chronic rhinosinusitis and are considered to be associated with more severe forms of disease with poor treatment outcome. The presentation and treatment outcome after endoscopic sinus surgery in patients of chronic rhinosinusitis and nasal polyposis have been analysed in this study. A prospective analysis of 90 patients of chronic rhinosinusitis who were classified into two groups depending on presence and absence of nasal polyps was performed in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
4
17
0
1
Order By: Relevance
“…The male to female ratio is 1.80:1. Which is in line with other previous studies (15)(16)9). The mean age of the study population was 40.88 ± 16.1 years .…”
Section: Quality Of Life In Patients With Chronic Rhinosinusitis Withsupporting
confidence: 92%
See 2 more Smart Citations
“…The male to female ratio is 1.80:1. Which is in line with other previous studies (15)(16)9). The mean age of the study population was 40.88 ± 16.1 years .…”
Section: Quality Of Life In Patients With Chronic Rhinosinusitis Withsupporting
confidence: 92%
“…In the NIKAKHLAGH et al study, the mean age of the population was 39.25 (22.66) (9) and in the study of Akarcay et al, The mean age of the study population was 36 (17). In the study of Satish et al, The mean age of the study population was 36 (16). furthermore, some study demonstrated the mean age of study population was 42 that similar to our study (18)(19)(20).…”
Section: Quality Of Life In Patients With Chronic Rhinosinusitis Withsupporting
confidence: 89%
See 1 more Smart Citation
“…Symptomatology in present study is comparable to that in a study conducted by Kennedy. 15 However Nair S et al concluded that headache and facial pains are commonest presenting symptoms in CRS patients as compared to nasal polyposis patients who present with nasal blockage, nasal discharge and reduced sense of smell. 16 Beside the clinical and radiological findings, the duration of symptoms is very important for diagnosis. In the present study, patients suffered from the disease for a much longer time, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…3) Non-closure of the peritoneum reduces the amount of surgical intervention and saves on valuable operating time and cost. 1,2,3,6,13,14,15,16 The objective of this study was to assess the effects of nonclosure and closure of the peritoneum at caesarean section.…”
Section: A Historical Perspectivementioning
confidence: 99%